Impact and risk assessment of chromium contaminated groundwater sites in saturated and unsaturated zones - Sibanyoni, John (University of the Free State, 2011)
A key challenge for chromium related activities, such as in ferrochromium industries, is the disposal of waste containing chromium slag or dust with hexavalent chromium (Cr(VI)). Various investigations have shown that hexavalent chromium is a serious concern to both environment and human health because of its mobility and carcinogenicity (Fendorf et al.; 2003). This study evaluates the impact of chromium on groundwater in the unsaturated and saturated zone by human related activities. A South African ferrochromium industry sector based in the Mpumalanga Province, (Middelburg) was selected as a case study to assess a waste dump of ferrochromium slag. The challenges regarding the dumping of slag are the oxidation of trivalent chromium (Cr(III)) to hexavalent chromium, as well as fine dust from the open arc furnaces which contain hexavalent chromium. At the case study site, the historic dump site (HDS), which is not lined, was previously used to dump various waste materials (since 1964), including but not limited to: - Ferrochromium slag - Phenols - Fine dust from open arc furnaces (with hexavalent chromium) - Filter cake (with hexavalent chromium) Literature studies indicate that trivalent chromium can be oxidised to hexavalent chromium Cr(VI) through presence of moisture, dissolved oxygen and manganese dioxide (MnO4) (EPA, 1994). The literature also indicates that concentration of hexavalent chromium Cr(VI) greater than 1 mg/l imparts a yellow colour (US EPA (1994) which was used as a visual indicator during field assessments at the HDS. The presence of hexavalent chromium was observed at the toe of the dumps and in low lying areas surrounding the dumps with elevated moisture contents. The presence of hexavalent chromium was also confirmed by monitoring results for both surface and groundwater. The mitigation that has taken place on site, involved the removal of hazardous waste such as fine dust and filter cake with hexavalent chromium from the HDS, and dumping it at a hazardous waste site (Holfontein). Other on-going mitigation at the dump is the usage of ferrous sulphate at the capturing point (infiltration gallery) to reduce hexavalent chromium to trivalent chromium through oxidation-reduction (redox) reaction process. This study has indicated that although some remedial approaches have been performed, the contamination still exists at the site. The findings of the study assessment have indicated the following: - Boreholes near the process plant indicated contamination by both trivalent chromium and hexavalent chromium.  Dam 4A and 4B have the highest concentration of hexavalent chromium as well as other constituents, such as sulphate (SO4). - Boreholes down-gradient of the HDS indicated pollution by hexavalent chromium, sulphate (SO4) and other parameters. - The western boreholes showed a trend of increasing pollution by sulphate (SO4), though not by trivalent or hexavalent chromium. Background boreholes did not show any pollution. - Contamination to the unsaturated zone is high but also differed when compared to contamination in saturated zones. - Contamination by hexavalent chromium is caused mainly by the fluctuating water table during water spraying (cooling) of hot slag, and due to precipitation in the rainy season.

Die grootste uitdagings van chroom-verwante aktiwiteite soos ferrochroom nywerhede is die verwydering van chroom afval (metaal slak), asook stof wat chroom ses (Cr (VI)) bevat. Verskeie ondersoeke het getoon dat die mobiliteit en kankergevaar van Cr (VI) skadelik kan wees vir beide die omgewing en menslike gesondheid (Fendorf et al.; 2003). Hierdie studie evalueer die impak van chroom-verwante aktiwiteite op grondwater sisteme. Beide die onversadigde en versadigde sones word bespreek. Die Suid-Afrikaanse ferrochroom bedryf, gesetel in Mpumalanga Provinsie, (Middelburg) is gekies as 'n gevallestudie, om die impak van die chroom metaal slak afval hoop op die grondwater sisteem te evalueer. Die moontlike oksidasie van ou slak is ‘n bekommernis. Verskeie literatuur studies het al bevind dat Cr (III) geoksideer kan word deur die teenwoordigheid van water, opgeloste suurstof en mangaandioksied (MnO4) (EPA, 1994). Die historiese stortings terein (HDS) is sedert 1964 in gebruik. Verskeie afvalmateriaal is daar gestort, insluitend (maar nie beperk tot): • Ferrochroom slak • Fenole • Fyn stof van die oop boogoond (met Cr6+) • Filter koek (met Cr6 +) Dit is bekend dat indien die konsentrasie van Cr (VI) groter is as 1 mg / l, dan verleen dit ‘n geel kleur (US EPA (1994) wat as 'n visuele aanwyser kan dien tydens veld opnames. Die teenwoordigheid van CR (VI) is waargeneem by die toon van die mynhope en laagliggende gebiede met ‘n hoë voginhoud. Die teenwoordigheid van Cr (VI) is ook bevestig in grondwater moniterings rekords. Sekere mitigerende maatreëls is aangepak op die HDS. Dit sluit in die verwydering van gevaarlike afval soos fyn stof en filter koek wat Cr (VI) bevat. Die impak van Cr (VI) word verder beperk deur yster sulfaat te gebruik om Cr (VI) te reduseer na Cr (III). Hierdie studie het bevind dat die regstellende aksies ‘n mate van verbetering veroorsaak het in sekere areas, maar dat die terein nog steeds besoedel is. Die volgende waarnemings is belangrik: • Boorgate naby die proses aanleg is besoedel met beide Cr (III) en Cr (VI). • Dam 4A en 4B is die mees-besoedeld met Cr (VI), sowel as ander chemiese komponente soos sulfaat • Boorgate in die ooste, stroom-af van die HDS is besoedel met Cr (VI), sulfaat en ander indikatore. • Boorgate in die weste toon dieselfde sulfaat besoedelings tendens aan, maar is nie besoedel met Cr (III) of Cr (VI). Boorgate wat die agtergrond grondwater kwaliteite in hierdie area moniteer toon geen impakte wat toegeskryf kan word aan die slik damme of die water damme nie. • Besoedeling van die onversadigde sone is hoog, maar wissel noemenswaardig oor tyd, in vergelyking met die besoedeling in versadigde sones. • Besoedeling deur Cr (VI) word hoofsaaklik veroorsaak deur die skommeling van die watertafel as gevolg van water wat op die warm slak gespuit word, en reënval gedurende die reënseisoen
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2011
Keywords: Receptors; Groundwater modelling; Ferrochromium slag; Saturated; Unsaturated; Hexavalent chromium; Groundwater contamination; Impact; Risk assessment; Groundwater -- Pollution; Pollution -- Risk management